Asset Prices, Financial Liberalization, and the Process of Inflation in Japan - Schinasi, Garry (IMF Working Papers; Working Paper ;, 1994)
The IMF Working Papers series is designed to make IMF staff research available to a wide audience. Almost 300 Working Papers are released each year, covering a wide range of theoretical and analytical topics, including balance of payments, monetary and fiscal issues, global liquidity, and national and international economic developments.